TRANSITION OF AGRICULTURE IN THE REPUBLIC OF SERBIA - achievements, effects and limitations - - Pejanović, Radovan; Milanović, Milan R.; Cvijanović, Drago (Economics of Agriculture, 2006)
The authors consider the current issues of the transition of agriculture in the Republic of Serbia, its achievements, effects and limitations. According to their opinion, the transitional reforms, so far, have not had the anticipated positive effects. The causes lie in the system. It is manifested in different ways: the developing instability of agriculture; unfavourable agrarian structure and decrease in productivity; decline of competitiveness; inefficiency of agrarian policy; the decrease in population and deterioration of villages; growing resistance to changes. The authors propose the measures and activities for overcoming the existing status, as to make the transition more efficient and bearable.